A focus on LBCL patients in partial remission in the CAR-T era - Tarantini, Giuseppe; Arcuti, Elena; Buquicchio, Caterina; Carluccio, Vera; De Santis, Gaetano; Germano, Candida Rosaria; Leo, Mariangela; Loconte, Daria Carmela; Mallano, Sonia; Miccolis, Rosanna Maria; Santeramo, Teresa Maria; Strafella, Vanda; et al. (Frontiers in Hematology, 2025)
The treatment paradigm for large B-cell lymphoma (LBCL) has undergone significant changes in recent years. Patients who fail to achieve a complete response (CR) after first-line therapy (1L) or relapse within 12 months are considered to have a poor prognosis. For these individuals, new therapeutic options, such as CAR-T cell therapy or bispecifics, have largely replaced traditional approaches, including chemotherapy, autologous hematopoietic stem cell transplantation (auto-HCT), and best supportive care. Accurate staging and evaluation of treatment response are critical, especially for patients achieving a partial response (PR) at the end of 1L. Patients with PR represent a distinct and less well-defined subgroup compared to those with stable or progressive disease or those achieving CR. These patients often have better outcomes than those with progressive disease (PD) or stable disease (SD), and their management remains less simple. Nowadays, prognostic classifications and treatment guidelines continue to evolve, offering new perspectives on how best to approach this subset. While immunotherapy with anti-CD19 CAR-T cells has become the standard of care for refractory LBCL, the role of salvage therapies may still be relevant for patients with PR who are not fully chemorefractory. This review underscores the importance of refining the definitions, prognostic assessments, and therapeutic strategies for patients with partial response, aiming to optimize outcomes in this challenging clinical context.